(untitled) (The Pakistan Development Review, 1992)
This is an English translation by Madhulika Reddy of the original Gennan book fIrst published by Verlag W. Kohlhammer in 1984, under the title: Nord-SUd Beziehungen: Geschichte-Politik-Wirtschaft. It deals with the complex economic relationship between the highly developed industrial countries of the North and the underdeveloped countries of the South in the perspective of history, sociology, and political economy. The nature, scope, and range of many diffIcult problems of North-South relations, in their historical context and in their socio-economic and political contents, give this book an aura of urgency and immediacy. These issues directly impinge not only on the lives of millions of human beings living in the developing countries of Asia, Africa, and Latin America who have been making strenuous efforts to solve the chronic problems of poverty, unemployment, underdevelopment, illiteracy, disease, and general social stagnation, but also affect the affluent people of the North who face the insidious threats of creeping recession, recurring unemployment, and falling productivity in their economies for lack of effective demand for their manufactures of high technology on the part of the disadvantaged developing countries.